Correlation analysis of biodegradable additives, temperature and loading toward tribology behaviour of musa aluminata balbisiana (MBS) oil - Muhammad, Noryani; A. Hamid, Husna; Omar, Ghazali; Masripan, Nor Azmmi (Italian Association of Chemical Engineering (AIDIC), 2022)
Identification of the effect of the tribological characteristics in lubricant application is a critical part of the experimental process. A correlation study is used to identify the effect of temperature, load and biodegradable additive on the coefficient of friction (COF) and specific wear (Ws) from the experimental data. Pearson correlation coefficient (r) and analysis of variance (ANOVA) are the statistical analysis used to identify the relationship between the parameters and the significant difference in response variable which are COF and Ws. Based on the result, there is a positive moderate linear relationship between temperature to both COF and Ws with a score of r between 0.354 to 0.676. In contrast, there is a negative linear relationship between load towards COF and Ws with a -0.285 to -0.460 score of r. There is approximately no correlation with the percentage of biodegradable additives respecting COF and Ws. The result also shows that there is no significant difference between COF and Ws using ANOVA testing with a p-value is more than 0.05. This work may facilitate improvements for other researchers to identify the variable in the experimental design process